Social Cognitive Theory on the Domestic Violence in Yogyakarta - Jati, Linda Puspita; Joebagio, Hermanu; Prasetya, Hanung (Journal of Maternal and Child Health, 2019)
Background: Domestic violence (also named domestic abuse or family violence) is violence or other abuse by one person against another in a domestic setting, such as in marriage or cohabitation. This study aimed to explore domestic violence in Yogyakarta using Social Cognitive Theory.Subjects and Method: This was a qualitative study using phenomenology approach. The study was carried out in a non-government organization, in Yogyakarta, in November 2018. The key informants included counselor at the Swadaya Masyarakat Rifka Annisa Yogyakarta and two victims of domestic violence. The data were collected by in-depth interview, participative observation, and document review. Results:There were variations of domestic violence, but the majority stemmed from external factors. Social environment, perceived gender equality, socioeconomic factor, and patriarchal culture affected the incidence of domestic violence. The educational background did not affect the risk of domestic violence. All victims experienced domestic violence due to gender inequality in decision making. Domestic violence could be physical or psychic.Conclusion: Domestic violence is affected by social environment, perceived gender equality, socioeconomic factor, and patriarchal culture. The educational background did not affect the risk of domestic violence.Keywords: domestic violence, Social Cognitive TheoryCorrespondence: Linda Puspita Jati. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami36 A, Surakarta 57126, Central Java, Indonesia. Email: linda.puspitajati@student.uns.ac.id. Mobile: +6285643538539. Journal of Maternal and Child Health (2019), 4(5): 326-334https://doi.org/10.26911/thejmch.2019.04.05.04